Research on Alliance-Based Local Chinese Teacher Training in Indonesia - Mettalina Chu, Binyu; Prativi, Martina; Mariati, Mariati; Tandiani, Alexandria (International Journal of Language Teaching and Education, 2026)
This study investigates the strategies for training local Chinese language teachers within the Maitreyawira School Alliance in Indonesia. Through questionnaire surveys and in-depth interviews, the research reveals that establishing a professional Chinese language expert team is key to improving the alliance‘s Chinese teaching standards. The expert team can provide systematic pedagogical guidance, enhance teachers‘ professional knowledge and instructional skills, promote innovation in teaching methods, and improve overall teaching quality. Although the current teacher training model has facilitated teacher development to some extent, yet challenges remain, including insufficient reliance on expert resources and the fragmentation of teaching materials. Therefore, this study recommends that the alliance strengthen collaboration with professional Chinese language education institutions, establish a dedicated expert guidance mechanism, optimize resource allocation, and address practical teaching challenges through continuous evaluation and feedback mechanisms—thereby supporting the ongoing improvement of local Chinese language education. This research offers valuable insights for the development of local language teacher training in other regions.